2023
DOI: 10.1098/rsta.2022.0185
|View full text |Cite
|
Sign up to set email alerts
|

Arctic freshwater impact on the Atlantic Meridional Overturning Circulation: status and prospects

Thomas W. N. Haine,
Ali H. Siddiqui,
Wenrui Jiang

Abstract: Arguably, the most conspicuous evidence for anthropogenic climate change lies in the Arctic Ocean. For example, the summer-time Arctic sea ice extent has declined over the last 40 years and the Arctic Ocean freshwater storage has increased over the last 30 years. Coupled climate models project that this extra freshwater will pass Greenland to enter the sub-polar North Atlantic Ocean (SPNA) in the coming decades. Coupled climate models also project that the Atlantic Meridional Overturning Circulation (AMOC) wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 106 publications
0
1
0
Order By: Relevance
“…It is known that changes to freshwater in the subpolar North Atlantic are happening [ 52 , 53 ] and model experiments have shown that increased freshwater input could disrupt the AMOC [ 55 ]. Therefore, an unknown aspect of the Atlantic overturning is how glacial melt from Greenland [ 47 ] and/or freshwater export from the Artic [ 56 ] might impact the AMOC and on what time scale. Furthermore, it is unknown on what time scales, and by which processes, changes in deep water formation at high latitudes might propagate south.…”
Section: New Challengesmentioning
confidence: 99%
“…It is known that changes to freshwater in the subpolar North Atlantic are happening [ 52 , 53 ] and model experiments have shown that increased freshwater input could disrupt the AMOC [ 55 ]. Therefore, an unknown aspect of the Atlantic overturning is how glacial melt from Greenland [ 47 ] and/or freshwater export from the Artic [ 56 ] might impact the AMOC and on what time scale. Furthermore, it is unknown on what time scales, and by which processes, changes in deep water formation at high latitudes might propagate south.…”
Section: New Challengesmentioning
confidence: 99%